2021
DOI: 10.1088/2053-1591/ac4439
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behaviors and discharge performance of Mg-Sn binary alloys as anodes for Mg-air batteries

Abstract: In this work, the self-corrosion and discharge performance of the as-cast Mg-xSn (x=1, 5, 9 wt.%) anodes for primary Mg-air batteries were studied through microstructure characterization, electrochemical testing and discharge experiments. With the increase of Sn content, the volume fraction of the Mg2Sn phase increases, promoting dendrite refining. According to the electrochemical test, the Mg-1Sn anode shows a higher open circuit potential, resulting in a stronger electrochemical activity. The polarization cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Mg-14Sn alloy shows different electrochemical behavior of Mg stripping/platting. This result is obtained due to the formation of the eutectic phase [7].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Mg-14Sn alloy shows different electrochemical behavior of Mg stripping/platting. This result is obtained due to the formation of the eutectic phase [7].…”
Section: Introductionmentioning
confidence: 81%
“…As a supplement for anode material, Magnesium has started to use for Mg-ion rechargeable batteries (MRBs), but MRB development is constrained by the undesirable passivation layer between Mg and electrolyte. Magnesium anodes have the benefits of a very negative potential (−2.37 V vs. standard hydrogen electrode, SHE), a low density (1.74 g cm −3 ) and a high Faradic capacity (2.2 Ah g −1 ) [7]. Adding Sn to the Mg-Zn alloy significantly increases the specific capacity and the anodic efficiency of the Mg-Zn anode.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Sn has been widely used due to its high theoretical specific capacity and low reaction voltage, leading to the formation of the Mg 2 Sn phase, which also has a high theoretical specific capacity and offers good electrochemical activity. 10,[22][23][24] However, while large amounts of the Mg 2 Sn phase in the Mg anode can facilitate corrosion, an optimal amount can increase the corrosion resistance and anode efficiency of the alloy. 25,26 Additionally, the Mg-1Sn alloy has been found to show the highest discharge capacity, which is mainly attributed to high electrochemical activity and the well-dispersed nanometric Mg 2 Sn phase in the Mg matrix.…”
mentioning
confidence: 99%
“…25,26 Additionally, the Mg-1Sn alloy has been found to show the highest discharge capacity, which is mainly attributed to high electrochemical activity and the well-dispersed nanometric Mg 2 Sn phase in the Mg matrix. 22 For instance, Wang et al 21 reported that the galvanic corrosion between the CaMgSn phase and the Mg matrix typically causes pitting corrosion in Mg-3Sn-1Ca-0.3 (Y, La) alloys. However, Song et al 27 found that on Ce addition in Mg-6Al alloy, the formation of a larger γ-(Al 4 Ce) phase could hinder the shedding of discharge products.…”
mentioning
confidence: 99%
“…2,3 The anode for seawater-activated batteries is mainly composed of magnesium alloy due to its negative electrode potential (−2.37 V vs SHE), low hydrogen evolution rate and high anode utilization. 4,5 According to the different cathode materials used for magnesium seawater-activated primary batteries, they can be classified into magnesium-hydrogen peroxide (Mg-H 2 O 2 ) batteries, magnesium-dissolved oxygen seawater batteries, magnesium-air batteries and magnesium-halide (Mg-halide) seawater-activated batteries. [6][7][8][9] Among them, Mg-halide seawater-activated batteries can discharge stably for a long time at low current densities (e.g.…”
mentioning
confidence: 99%